The Evolution of the Budgetary Concept in the Federal Government (Book). - Lemke, B. C. (The Accounting Review, 1946)
Abstract Reviews the book "The Evolution of the Budgetary Concept in the Federal Government," edited by Catheryn Seckler-Hudson.